2021
DOI: 10.3758/s13423-021-01958-1
|View full text |Cite
|
Sign up to set email alerts
|

Gotcha: Working memory prioritization from automatic attentional biases

Abstract: Attention is an important resource for prioritizing information in working memory (WM), and it can be deployed both strategically and automatically. Most research investigating the relationship between WM and attention has focused on strategic efforts to deploy attentional resources toward remembering relevant information. However, such voluntary attentional control represents a mere subset of the attentional processes that select information to be encoded and maintained in WM (Theeuwes, Journal of Cognition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 111 publications
1
8
0
Order By: Relevance
“…Indeed, previous studies have shown that top-down manipulations with presentation times shorter than 2000 ms can have strong effects on VWM performance for equally salient stimuli (Bays et al, 2011;Dube et al, 2017;Emrich et al, 2017;Klink et al, 2017;Ravizza et al, 2021; see also, Ravizza and Conn, 2022). Some of these studies have also looked at the interplay of salience, presentation time and top-down influences, but none of them contained a nonconfounded and direct manipulation of to-be-remembered stimuli's salience (for a discussion, see Constant & Liesefeld, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, previous studies have shown that top-down manipulations with presentation times shorter than 2000 ms can have strong effects on VWM performance for equally salient stimuli (Bays et al, 2011;Dube et al, 2017;Emrich et al, 2017;Klink et al, 2017;Ravizza et al, 2021; see also, Ravizza and Conn, 2022). Some of these studies have also looked at the interplay of salience, presentation time and top-down influences, but none of them contained a nonconfounded and direct manipulation of to-be-remembered stimuli's salience (for a discussion, see Constant & Liesefeld, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, previous studies have shown that top-down manipulations with presentation times shorter than 2,000 ms can have strong effects on VWM performance for equally salient stimuli (Bays et al, 2011; Dube et al, 2017; Emrich et al, 2017; Klink et al, 2017; Ravizza et al, 2021; see also, Ravizza & Conn, 2022). Some of these studies have also looked at the interplay of salience, presentation time and top-down influences, but none of them contained a nonconfounded and direct manipulation of to-be-remembered stimuli’s salience (for a discussion, see Constant & Liesefeld, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…With this manipulation, participants should be highly incentivized to focus their available resources on less salient targets to maximize their gains. Recently, it has been called into question, whether reward can increase overall VWM performance (van den Berg et al, 2023), but that reward can affect the distribution of limited cognitive resources among concurrently presented stimuli is well established (reviewed in, e.g., Anderson, 2019) and, in fact, such an effect has been demonstrated also in VWM tasks (Allen & Ueno, 2018; Klink et al, 2017; for a VWM-focused review, see Ravizza & Conn, 2022). As we believe that implementing top-down control takes more than a few hundred milliseconds, we expected (preregistration: https://osf.io/fxwyp) an effect of salience for displays presented for 350 ms.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, whatever causes this trial to be particularly easy has little to do with working memory storage, or higher level processes that are thought to occur in working memory such as the formation of perceptual chunks (Nassar et al, 2018). Instead, attention appears to be biased toward the probed item on this trial during study, and remains so throughout the retention interval as would be expected from bottom-up, automatic attentional biases, which have been shown to have large effects on working memory performance (e.g., Constant & Liesefeld, 2021;Ravizza & Conn, 2022).…”
Section: Discussionmentioning
confidence: 99%